THE EFFECT OF SETS LEARNING MODEL AND SCIENTIFIC ATTITUDE TOWARD STUDENT’S PHYSICS ACHIEVEMENT - Amelia, Riski; Supriyati, Yetti; Indrasari, Widyaningrum (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The purpose of this study is determine the effect of science, environment, technology, and society (SETS) learning model and scientific attitude toward student’s physics achievement in XI grade student. This study was conducted at SMAN 2 Indramayu. This study used quasi experiment method with Two Way Anova design. There are 64 students as the sample and it was selected by purposive sampling. Students in experimental group learned through Science, Environment, Technology, and Society. Meanwhile, in control group, students learned through Inquiry Learning. The result of this study are: the student’s achievement given by Science, Environment, Technology and Society is higher than Inquiry; there is influence of interaction between learning models and scientific attitude toward student’s achievement; student’s achievement given by Science, Environment, Technology, and Society is higher than Inquiry in group of student’s with high scientific attitude; and student’s achievement given by Science, Environment, Technology, and Society is lower than Inquiry in group of student’s who have low scientific attitude.